Analisis Sikap Terhadap Pembelajaran Matematika Siswa Kelas V SDN 20 Desa Langsat Hulu Kecamtan Sentajo Raya Kabupaten Kuantan Singingi - Mega Julia (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Mathematics is an important science in efforts to develop critical and systematic ways of thinking in solving problems. Mathematics has an abstract nature in its concepts, facts, operations and principles. This makes mathematics a subject that is difficult to understand directly. According to UNESCO, Indonesia ranks 45th out of 50 countries in students' ability to understand mathematics. Student difficulties can be caused by various factors such as self-aspects related to feelings, beliefs, ideals and attitudes. This difficulty in understanding mathematics results in an inappropriate attitude towards mathematics. This research aims to analyze the extent of student attitudes towards learning mathematics among students at SDN 20 Langsat Hulu Village. Then the subjects of this research were 25 class V students. The research method used is descriptive qualitative with data collection procedures in the form of questionnaires. This research shows that students' attitudes towards mathematics are in the good category.